Improving Senior High School Students' Critical Thinking Skills on Electron Configuration through a Deep Learning Approach - Ruslia Mursid; Jovaline A Rungkat; Cosmas Poluakan (PT. AHLAL PUBLISHER NUSANTARA, 2026)
Objective: This study investigates the effectiveness of a deep learning approach in enhancing senior high school students' critical thinking skills, specifically on the topic of electron configuration—an abstract concept in chemistry that often leads to surface learning. Method: A quasi-experimental method with a nonequivalent control group design was employed. The sample consisted of 52 tenth-grade students (26 in the experimental group, 26 in the control group) from SMA Negeri 5 Ternate, Indonesia. The experimental group was taught using the deep learning approach (characterized by meaningful, mindful, and joyful learning), while the control group received conventional instruction. A critical thinking skills test, comprising nine essay items validated for content and construct validity (r > 0.444), reliability (Cronbach’s α = 0.914), discrimination index, and difficulty level, was used for pre-test and post-test measurements. Data were analyzed using descriptive statistics, normality tests (Shapiro-Wilk), homogeneity tests (Levene), and an independent sample t-test. Results: The post-test mean score of the experimental group (M = 63.38, SD = 7.85) was significantly higher than that of the control group (M = 58.19, SD = 7.76), with a mean difference of 5.19 points. The independent sample t-test revealed a statistically significant difference between the two groups (t = -2.398, df = 50, p = 0.020 < 0.05), leading to the rejection of the null hypothesis. Furthermore, students in the experimental group demonstrated improved abilities in interpreting, analyzing, evaluating, inferring, and explaining electron configuration concepts, particularly in applying the Aufbau principle, Hund's rule, and the Pauli exclusion principle. Conclusion: The deep learning approach positively and significantly contributes to improving students' critical thinking skills in learning electron configuration. This approach fosters active engagement, conceptual understanding, and scientific reasoning, making it a recommended pedagogical strategy for chemistry education. Keywords: deep learning, critical thinking skills, electron configuration, chemistry learning, quasi-experiment